Gold medal summer - Freitas, Donna. (Arthur A. Levine Books, 2012)
After fourteen-year-old Joey experiences her first kiss and learns that her best friend wants to quit competitive gymnastics, she considers giving up her dream of winning gold medals in order to have a normal life, even as her sister and assistant coach urge her to reach a new level.